2015
DOI: 10.1299/jtst.2015jtst0001
|View full text |Cite
|
Sign up to set email alerts
|

Review of boiling explosion due to homogeneous nucleation in theoretical and experimental approach

Abstract: Boiling explosion phenomena are experimentally observed in various fields and are applied in macro-and nano-fields. Analysis of boiling explosion has been recently conducted from a non-equilibrium point of view to understand the experimental results under some special conditions such as linear quick heating, ultra high heat flux pulse heating, and liquid contact with high temperature surface. Analytical result is shown to agree well with those experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…To prevent the oxidation of Sn, ethanol is used as the liquid phase. The spinodal temperature of ethanol is assumed to be the critical temperature of ethanol, 513 K, 50 higher than the melting point of Sn. Thus, Sn particles can more easily melt without the formation of TINBs at the particle surface during heating.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To prevent the oxidation of Sn, ethanol is used as the liquid phase. The spinodal temperature of ethanol is assumed to be the critical temperature of ethanol, 513 K, 50 higher than the melting point of Sn. Thus, Sn particles can more easily melt without the formation of TINBs at the particle surface during heating.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the case of water under 1 atm, it lies between 100 °C, the boiling point, and ≈ 320 °C, the spinodal decomposition temperature. [43][44][45][46] The calculation results shows that the region over 320 °C expands from region B to A as q A increases. We therefore found that the value of q A is the key factor controlling the bubble size and position.…”
Section: Microfluidic Control With Gold Micropetalsmentioning
confidence: 94%